Autistics appear different, but also are different, and this should be valued. (2019) - Dawson, Michelle; Cowen, Tyler
Abstract: We agree that autistics' unusual overt behaviors don't necessarily mean reduced social motivation. But Jaswal & Akhtar maintain that, while autistics may appear socially uninterested, their social interest is in fact typical and indeed must be to avoid multiple poor outcomes. This problematic idealization of social typicality deflects attention from important differences in autistic cognition and interests, which should be valued.